2015
DOI: 10.1111/exd.12722
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts support migration of monocyte‐derived dendritic cells by secretion of PGE2 and MMP‐1

Abstract: The outcome of a cutaneous immune response is critically dependent upon the ability of dendritic cells (DC) to migrate from skin to the draining lymph nodes - a process that is influenced by the cutaneous tissue microenvironment. Here, the role of fibroblasts - a major component of the dermal microenvironment - on the migratory capacity of monocyte-derived DC (MoDC) was investigated in a 3D collagen I matrix. Indeed, dermal fibroblasts supported the migration of pre-activated MoDC through a 3D collagen I matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…COX-2 and its downstream products have been implicated in promoting cell migration in a variety of cell types [1517]. To determine whether TNF-α-induced COX-2 expression was involved in myofibroblast migration, 18Co cells were first exposed to TNF-α (10 ng/ml) over 4 h and COX-2 expression was analyzed by Western blot.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…COX-2 and its downstream products have been implicated in promoting cell migration in a variety of cell types [1517]. To determine whether TNF-α-induced COX-2 expression was involved in myofibroblast migration, 18Co cells were first exposed to TNF-α (10 ng/ml) over 4 h and COX-2 expression was analyzed by Western blot.…”
Section: Resultsmentioning
confidence: 99%
“…COX-2 is a known downstream target of TNF-α in colonic myofibroblasts [1, 4, 18, 25], is up-regulated in the setting of intestinal inflammation [26, 27], and regulates cell migration in a number of cell types [1517]. Having demonstrated that TNF-α stimulates COX-2 expression in a P38 MAPK-dependent manner, we sought to determine whether COX-2 was involved in TNF-α-mediated myofibroblast migration.…”
Section: Resultsmentioning
confidence: 99%
“…Human MoDCs were generated from CD14‐positive monocytes from whole blood using CD14 + Cell Isolation Kit (Miltenyi, Bergisch Gladbach, Germany) according to manufacturer's instructions. Monocytes were cultivated in DC medium as described .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in cervical lesions, PGE 2 expression is higher compared with in normal tissues (9)(10)(11). Additionally, certain studies have revealed that PGE 2 modulates the migration of DCs (12,13). Therefore, PGE 2 may be associated with changes in DCs in cervical lesions.…”
Section: Introductionmentioning
confidence: 99%